Constitutional Law, Ecosystems, and Indigenous Peoples in Colombia: Biocultural Rights and Legal Subjects. Issue 3 (8th November 2020) - Macpherson, Elizabeth; Torres Ventura, Julia; Clavijo Ospina, Felipe
Abstract: The recognition of rivers and related ecosystems as legal persons or subjects is an emerging mechanism in transnational practice available to governments in seeking more effective and collaborative natural resource management, sometimes at the insistence of indigenous peoples. This approach is developing particularly quickly in Colombia, where legal rights for rivers and ecosystems are grasping onto, and evolving out of, constitutional human rights protections. This enables the development of a new type of constitutionalism of nature. Yet legal rights for rivers may obscure the rights of indigenous peoples and their role in resource ownership and governance. We argue that the Colombian river cases serve as a caution to courts and legislatures elsewhere to be mindful, in devising ecosystem rights, of the complex and interrelated rights, interests and tenures of indigenous peoples and local communities.